Obesity surgery and risk of cancer. Issue 12 (13th July 2018) - Mackenzie, H; Markar, S R; Askari, A; Faiz, O; Hull, M; Purkayastha, S; Møller, H; Lagergren, J
Abstract: Background: Obesity increases the risk of several types of cancer. Whether bariatric surgery influences the risk of obesity-related cancer is not clear. This study aimed to uncover the risk of hormone-related (breast, endometrial and prostate), colorectal and oesophageal cancers following obesity surgery. Methods: This national population-based cohort study used data from the Hospital Episode Statistics database in England collected between 1997 and 2012. Propensity matching on sex, age, co-morbidity and duration of follow-up was used to compare cancer risk among obese individuals undergoing bariatric surgery (gastric bypass, gastric banding or sleeve gastrectomy) and obese individuals not undergoing such surgery. Conditional logistic regression provided odds ratios (ORs) with 95 per cent confidence intervals. Results: In the study period, from a cohort of 716 960 patients diagnosed with obesity, 8794 patients who underwent bariatric surgery were matched exactly with 8794 obese patients who did not have surgery. Compared with the no-surgery group, patients who had bariatric surgery exhibited a decreased risk of hormone-related cancers (OR 0·23, 95 per cent c.i. 0·18 to 0·30). This decrease was consistent for breast (OR 0·25, 0·19 to 0·33), endometrium (OR 0·21, 0·13 to 0·35) and prostate (OR 0·37, 0·17 to 0·76) cancer. Gastric bypass resulted in the largest risk reduction for hormone-related cancers (OR 0·16, 0·11 to 0·24). Gastric bypass, but not gastric banding or sleeve gastrectomy, was associated with an increased risk of colorectal cancer (OR 2·63, 1·17 to 5·95). Longer follow-up after bariatric surgery strengthened these diverging associations. Conclusion: Bariatric surgery is associated with decreased risk of hormone-related cancers, whereas gastric bypass might increase the risk of colorectal cancer. Abstract : Obesity affects cancer risk